2014
DOI: 10.1080/09571736.2014.947382
|View full text |Cite
|
Sign up to set email alerts
|

T(w)o and fro: using the L1 as a language teaching tool in the CLIL classroom

Abstract: This article describes a small in-class study which sought to explore the effectiveness (or not) of using the emerging bilingual skills of the students as a teaching and learning tool in a Geography through English CLIL classroom in Northern Italy. In particular, the study sought to examine whether and to what extent the use of codeswitching / translanguaging between the native language and the language of instruction during content-related tasks might prove a useful technique for highlighting particular gramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Other studies on translanguaging in CLIL that focus on classroom data have revealed that translanguaging is not only a feature of many CLIL classrooms, but also that translanguaging practices do indeed serve various purposes such as facilitating content, managing the classroom, creating language awareness, or signalling alignment, to name just a few (see e.g. Gallagher & Colohan, 2017;Gierlinger, 2015;Paulsrud 2014Paulsrud , 2016Toth 2018). Thus, translanguaging practices can enrich the CLIL classroom on multiple levels.…”
Section: Translanguaging and Clilmentioning
confidence: 99%
“…Other studies on translanguaging in CLIL that focus on classroom data have revealed that translanguaging is not only a feature of many CLIL classrooms, but also that translanguaging practices do indeed serve various purposes such as facilitating content, managing the classroom, creating language awareness, or signalling alignment, to name just a few (see e.g. Gallagher & Colohan, 2017;Gierlinger, 2015;Paulsrud 2014Paulsrud , 2016Toth 2018). Thus, translanguaging practices can enrich the CLIL classroom on multiple levels.…”
Section: Translanguaging and Clilmentioning
confidence: 99%
“…In Italy, Agolli (2015) describes a pre-CLIL initiative known as CLSL -Content and Languages Shared Learning -whereby EFL teachers are tasked with reinforcing and expanding on content introduced in the L1 but this is at primary level and although the syllabus is bilingual, the classrooms are still envisaged as monolingual. One of the few studies addressing planned translanguaging in secondary education (albeit not disambiguating between translanguaging and codeswitching) is Gallagher and Colohan (2014). Their data-gathering involved a 'twisted' dictation activity with both content and language related goals (reviewing the topic of climate and highlighting adverbial placement).…”
Section: Translanguaging In Clilmentioning
confidence: 99%
“…Appendix CLIL study ("√" means that this element is included) Gallagher and Colohan [85] L1 can be used as an auxiliary tool in CLIL.…”
Section: √ √ √mentioning
confidence: 99%